A methods engineering study on Automated Technology Philippines Incorporated - Bias, Maylyn C. (College of Engineering, 2005)
ATEC is familiar with the benefits that they can reap in applying the techniques in methods engineering, the proof of which is the presence of an IE department within their company that continuously monitor their production efficiency, quality control and inspection and other aspects dealing with the company operations. The study concentrated on the critical manual operations, which is the die coating operation, and other minor factors that affects their long production cycle. The study did not give much attention to their automated operations, since the machines' operation are considered uniform and standard. The study found some improvements that can be made in the die coating operation, like on the manual mixing of coating material, which is critical because this will determine if the chips could withstand the following operations to which it will be subjected. Other problems found focused on workers behaviour during operation, like frequent interaction with other employees. And one problem identified is the lack of safety instructions on how to handle the machine during their SOP (standard operating procedure). The said problems are included in the two recognized primary problems which are the long production cycle time and failure in maintaining worker safety and well being in some areas. Recommendations were generated, some of which are to build divisions between the workstations of the workers to avoid frequent interaction, revise the existing rules and reinforce the implementation of the rules. It is also recommended to look for a substitute raw material and more efficient oven to shorten production cycle. In order to ensure workers' safety and well being, it is recommended that workers assigned to Hipot testing, molding and trim/singulate area by provided with earplugs or earmuffs to lessen the noise they are being subjected to. It is also recommended that those areas be provided with adequate lighting to avoid future vision problems.